Leaf anatomy and biomineralization in Empetrum rubrum Valh ex Willd. (Ericaceae) - Fernández Pepi, María Gabriela (2012)
The present paper describes and illustrates features of Empetrum rubrum epidermis and transverse leaf section. It also describes and quantifie siliceous and calcium phytoliths.Biomineralization quantification is expressed as the media biomineral content (% from dry weight) with values of 1.58% ± 0.51 in silica phytoliths and 0.82% in calcicum phytoliths. E. rubrum is a native species from the austral end of South America. We here compare features of its leaf anatomy and biomineralization quali-quantifications with those from E. nigrum, a native species from the northern hemisphere. The comparison between the characters described for this species and those from macroremains and phytoliths recovered from surface soils provides valuable tools for taxonomical, ecological, paleontological and paleoecological studies. Knowledge of said characters further provides valuable information to infer changes in plant communities in the recent past as well as insight into the environmental and soil conditions at the time when such changes took place.